Evaluasi Layanan Penjualan Makanan Secara Offline dan Online - Yehuda Anugrah Kristanto; Albert Kriestian Novi Adhi Nugraha (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
This study examines the differences between attribute importance and product evaluation of food services offline and online. The research is a quantitative approach in nature. The research population is all people who have bought food offline and online, with a sample of 262 people. The variables in this study consist of product attributes and purchase decisions. The product attributes in this study consist of varied menus, low prices, promos, practicality, service speed, suitability of product descriptions with the served food, and store ambiance. An online questionnaire is a tool for data collection. The results showed (1) there is no difference in attribute importance between the two preference groups except for ambiance in food consumption, and (2) there are differences in service evaluation between the two preference groups when evaluating offline and online food service.